2021
DOI: 10.3906/sag-2101-406
|View full text |Cite
|
Sign up to set email alerts
|

Is CONUT score a prognostic index in patients with diffuse large cell lymphoma?

Abstract: Background/Aim: The aim of the study was to evaluate the effect of Controlling Nutritional Status (CONUT) score on the prognosis in patients with diffuse large B-cell lymphoma(DLBCL). Materials and Methods:The present study was a retrospective study. The CONUT score was calculated based on serum albumin, total cholesterol and lymphocyte levels. This study included a total of 266 patients, 131(49.2%) were female and 135(50.8%) were male. The median follow-up period was 51 months (range: 1-190). Results:The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Six studies ( 10 , 14 18 ) investigated the OS of patients with hematologic malignancy. Following the results of the heterogeneity test with an I ² value 58.3 and a P-value of 0.035, the random-effects model was chosen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies ( 10 , 14 18 ) investigated the OS of patients with hematologic malignancy. Following the results of the heterogeneity test with an I ² value 58.3 and a P-value of 0.035, the random-effects model was chosen.…”
Section: Resultsmentioning
confidence: 99%
“…ÇAĞLIYAN A et al. reported that a high CONUT score group was correlated to a worse PFS in patients with DLBCL after univariate analysis ( 18 ). Multivariate analysis also showed that the CONUT score was an independent prognostic factor for PFS.…”
Section: Resultsmentioning
confidence: 99%
“…It can comprehensively reflect the nutritional status of patients by assessing their Alb, TC, LYM, and other aspects, such as protein reserves, calorie consumption, and immune defense status ( 12 , 13 ). The CONUT score can be used to comprehensively assess the nutritional status of patients with non-HIV-infected lymphoma and can be a sensitive predictor of prognosis in patients with lymphoma ( 14 , 15 ). As the most commonly used clinical index in the CONUT score to evaluate the nutritional status of the patient’s body functions, Alb is reduced in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The CONUT score has been proven not only to correlate with malnutrition grade [ 11 ] but also to have a high predictive value concerning clinical outcomes and morbidity. For example, in patients with cancer, a higher CONUT score predicts a lower overall survival, a lower progress/recurrence-free survival, and a lower cancer-specific survival after surgery [ 15 , 16 ], and a similar predictive value has also been observed for non-solid tumors and other hematologic disorders [ 17 , 18 , 19 ]. However, the CONUT score has also been investigated as a predictor of morbidity or mortality in various conditions other than malignancies, for example, in patients undergoing liver transplant [ 20 ] or heart bypass surgery [ 21 ], in patients with acute heart failure [ 22 ], or in patients with pulmonary embolism [ 23 ].…”
Section: Introductionmentioning
confidence: 95%